Alleviation of Toxic Effects of Untreated Wastewater on Selective Vegetables Using Soil Organic Amendments - Muhammad İmran Khan; Zaffar Malik; Ghulam Hassan Abbasi; Muhammad Babar Javed; Sardar Alam Cheema; Muhammad Dawood; Muhammad Rafey; Malik Noman Mansha (Journal of Agricultural Sciences)
In this work, a pot experiment was conducted to evaluate the effect of organic amendments in alleviation of toxicity of untreated domestic wastewater to okra (Abelmoschus esculentus) and purslane (Portulaca oleracea). Three organic amendments including farm yard manure (FYM), poultry manure (PM) and bagasse ash (BGA) at the rate of 1% and 3% were applied to the soil to evaluate their positive impact on vegetable plants. Results showed that untreated wastewater impeded the growth of both vegetables and increased uptake of heavy metals (HMs) (i.e. Cu, Ni, Pb and Zn) by plants whereas organic amendments significantly improved the growth of plants and decreased the uptake of HMs. Shoot and root lengths and dry weights of plants were boosted by the FYM and PM, while chlorophyll a and b and carotenoids were enhanced by PM and BGA amendments. Interestingly, reduced HMs uptake was found where 3% of BGA or FYM were applied. Overall the results of this study showed that all three organic amendments were useful for improving growth of vegetables and alleviating the phytotoxicity of untreated wastewater and uptake of HMs by plants. Our findings suggest that these organic materials could be useful for improving agricultural productivity in untreated wastewater irrigated areas.